Mechanical response of outer frames in tuning fork gyroscope model with connecting diamond-shaped frame - Vu Van The; Tran Quang Dung; Chu Duc Trinh (Vietnam Journal of Mechanics)
In tuning fork micro-gyroscopes, two outer frames are connected by using the linking elements. The driving vibrations of the two outer frames are required to be exactly opposite to generate the opposite sensing modes perpendicular to driving direction. These opposite driving vibrations are provided by a mechanical structure named the diamond-shaped frame. This paper presents mechanical responses of two outer frames in a proposed model of tuning fork gyroscope when an external force with different types is applied to them. The results show that the presence of a diamond-shaped frame guarantees the absolute anti-phase mode for the driving vibrations of outer frames.